Anatomic Relationship Between the Spinal Accessory Nerve and Internal Jugular Vein in the Upper Neck during Neck Dissection: An Observational Study - Mulmi, Rajan Govinda; Sah, Bajarang Prasad; Chhetri, Shyam; Paudel, Deepak; Mishra, Sudeep; Neupane, Durga (Birat Journal of Health Sciences, 2025)
Objectives: To find the intraoperative relationship between the spinal accessory nerve (SAN) and the internal jugular vein (IJV) in the upper neck, at the level of the superior border of the posterior belly of the digastric (PBD) muscle. Methods: A prospective study was carried out in the Department of Otorhinolaryngology and Head & Neck Surgery, B. P. Koirala Institute of Health Sciences, Dharan from December 2019 to November 2020. The study population involved all the patients who underwent unilateral or bilateral level II neck dissection for the treatment or diagnosis of head and neck pathology and procedure where the relationship between SAN and IJV could be assessed. Results: Thirty-nine patients were enrolled in the study who met the inclusion criteria. The mean age of the patient was 49.59 years with an SD of ±12.571 years. Unilateral neck dissections were done for 31 (79.48%) and bilateral neck dissections were done for 8 (20.51%) cases. The SAN was positioned lateral to the IJV at the superior margin of the posterior belly of the digastric muscle in 35 (74.46%) of neck dissections, medial to the IJV at this level in nine cases (19.14%) and the SAN traveled directly through the IJV in three cases (6.38%). Conclusion: The posterior belly of the digastric muscle is the most common location at which the SAN is encountered. The vast majority of the SANs coursed lateral to the IJV at the level of the posterior belly of the digastric muscle. Given the morbidities associated with iatrogenic injury to the SAN, surgeons should also be aware of the rare relationship between these structures.